DEVELOPMENT OF AUGMENTED REALITY-BASED LEARNING BOOKS TO IMPROVE STUDENT PREPAREDNESS FOR LANDSLIDE DISASTERS AT SMA NEGERI 1 KERJO, KARANGANYAR REGENCY - Lintang Ronggowulan; Pipit Wijayanti; Rahning Utomowati; Gentur Adi Tjahjono; Ardia Tiara Rahmi; Dwi Puspitasari (GeoEco, 2026)
Student preparedness in facing landslide disasters is an important aspect in disaster risk reduction in educational units. However, disaster learning in secondary schools is still dominated by conventional teaching materials that lack visualization and have not been optimally integrated with the Disaster Safe Education Unit Program (SPAB). This study aims to develop SPAB-based textbooks equipped with Augmented Reality (AR) technology to improve students' understanding and preparedness for landslide disasters. The study used the Research and Development (R&D) method with the ADDIE model. The research subjects consisted of 32 students of Class XII. F7 SMA Negeri 1 Kerjo. The research instrument used validation by material experts and media experts. Based on the research results, it can be concluded that the Disaster Safe Education Unit (SPAB)-based learning book enriched with Augmented Reality (AR) technology is declared feasible and effective for use in landslide disaster mitigation learning. The validation results showed a score of 79.2 from material experts and 80 from media experts, both of which are in the feasible category. Effectiveness testing on 32 students showed improved learning outcomes, with an average score increasing from 56.2 in the pretest to 83 in the posttest, and an N-Gain value of 56%, which is considered quite effective. These findings confirm that integrating SPAB-based textbooks with AR visualizations can significantly improve students' understanding and preparedness, while also serving as an alternative, innovative learning medium relevant to disaster education in schools.